Planning and Evaluation of UAV Mission Planner for Intralogistics Problems - Cavalcante, Thiago Rodrigo Felix; Bessa, Iury Valente de; Cordeiro, Lucas Carvalho (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2017)
We describe and evaluate the development of mission planners in intralogistics for a commercial unmanned aerial vehicle equipped with a robotic gripper in an industrial environment, which consists of an input warehouse, production lines, and a product depot. In this particular study, the planner produces the needed commands for carrying out a given mission, which includes the delivery of inputs picked up from the warehouse to the production line until the final product is delivered to the client (product depot). We propose two different approaches for mission planning: in the first approach, a simple heuristic is used to solve the mission problem, where a UAV obtains the needed inputs to produce a product from the warehouse, and then it brings the product to the respective production line and waits to finish its production; in the second approach, a technique with task scheduling (production process) is employed; both approaches follow a set of production rules. In addition, a novel evaluation methodology for mission planner algorithms is proposed in order to verify the cost of both approaches, measure the execution time, and compare those results with the optimum cost obtained with the IBM ILOG CPLEX optimizer.